2012
DOI: 10.1177/1748048512458559
|View full text |Cite
|
Sign up to set email alerts
|

The three alternative journalisms of Africa

Abstract: Much African journalism scholarship has had a critical stand towards 'Western' journalism models. The criticism has resulted in the submission of alternative African journalism models such as ujamaa journalism, ubuntu journalism and oral discourse journalism. The present article reviews a number of significant contributions to normative African journalism models over the past 50 years and argues that they constitute three major streams: journalism for social change, communal journalism and journalism based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Steele (2013, 355), therefore, concluded that "although the principles and (roles) of journalism may indeed be universal, they are understood and expressed within particular political and cultural contexts." In many African contexts, for example, journalistic role models fall into three major domains: journalism for social change, communal journalism, and journalism based on oral discourse (Skjerdal 2012).…”
Section: Journalistic Roles In the Literaturementioning
confidence: 99%
“…Steele (2013, 355), therefore, concluded that "although the principles and (roles) of journalism may indeed be universal, they are understood and expressed within particular political and cultural contexts." In many African contexts, for example, journalistic role models fall into three major domains: journalism for social change, communal journalism, and journalism based on oral discourse (Skjerdal 2012).…”
Section: Journalistic Roles In the Literaturementioning
confidence: 99%
“…The fact that Ghanaian press coverage is lopsided and unable to engage in this positive interpretation, as discovered in this study, is rather a confirmation of their incapacity to act contrary to their ideological understanding of news discourse, which has been handed down to them over centuries as part of a professional co-optation. This midpoint-position ambivalence of belonging to a globalised journalism profession and being a custodian of national/regional discourse, as indicated in the work Terje Skjerdal (2012), strongly accounts for the differences in the findings of Flamenbaum on social media and this study's finding on the mainstream print media.…”
Section: Conditions and Representationsmentioning
confidence: 66%
“…An example of an appeal to "African values" is Francis Kasoma's (1994Kasoma's ( , 1996 notion of "Afriethics," which rejects Western normative frameworks and counterposes an African value system that privileges communalism and an orientation towards the family and clan over individualism. Appeals to "African values" have often been criticized for their tendency to essentialize African culture and identity, without acknowledging the interpenetration of African and Western values in a globalized context (Banda 2009;Skjerdal 2012). Additionally, such appeals have served to justify repression of media freedom in many African countries (see Bourgault 1995;Karikari 2007).…”
Section: Threats To Public Knowledge 2: Coercive Forcementioning
confidence: 99%